Model Perancangan Organisasi Berdasarkan Dorongan Pasar - Cecep Hidayat (Bina Nusantara University, 2012)
Designing Market-Driven Organizations reflects the needs of the customer in the design, roles, and organizational activities. This paper has objectives to review the definitions, concepts, and models relating to the organization based on market needs. The research method used is based on the study of literature references are used as discussion material. The main theories used are the marketing concept, customer value, and design organizations. Conclusion the results of the analysis indicate that the philosophy or concept of marketing is used as the basic design of the organization based on market forces are still relevant to today's conditions.